Right ventricular and cyclic guanosine monophosphate signalling abnormalities in stages B and C of heart failure with preserved ejection fraction. (3rd September 2021) - Petit, Thibault; Claessen, Guido; Claeys, Mathias; La Gerche, Andre; Claus, Piet; Ghysels, Stefan; Delcroix, Marion; Ciarka, Agnieszka; Droogne, Walter; Van Cleemput, Johan; Willems, Rik; Voigt, Jens‐Uwe; et al.
Abstract: Aims: Identifying early right ventricular (RV) dysfunction and impaired vasodilator reserve is challenging in heart failure with preserved ejection fraction (HFpEF). We hypothesized that cardiac magnetic resonance (CMR)‐based exercise imaging and serial cyclic guanosine monophosphate (cGMP) measurements can identify dynamic RV‐arterial uncoupling and responsiveness to pulmonary vasodilators at early stages of the HFpEF syndrome. Methods and results: Patients with HFpEF ( n = 16), impaired left ventricular relaxation due to concentric remodelling (LVCR, n = 7), and healthy controls ( n = 8) underwent CMR at rest and during supine bicycle exercise with simultaneous measurements of central haemodynamics and circulating cGMP levels, before and after oral administration of 50 mg sildenafil. At rest, mean pulmonary artery pressures (mPAP) were higher in HFpEF, compared with LVCR and controls (27 ± 2, 18 ± 1, and 11 ± 1, respectively; P = 0.01), whereas biventricular volumes, heart rate, and stroke volume were similar. During exercise, LVCR and HFpEF had a greater increase in the ratio of mPAP over cardiac output than controls (5.50 ± 0.77 and 6.34 ± 0.86 vs. 2.24 ± 0.55 in controls, P = 0.005). The ratio of peak exercise to rest RV end‐systolic pressure‐volume, a surrogate of RV contractility, was significantly reduced in LVCR and HFpEF (2.32 ± 0.17 and 1.56 ± 0.08 vs. 3.49 ± 0.35 in controls, P < 0.001) and correlated with peak exercise VO2 ( R 2 = 0.648, P < 0.001). cGMP levels increased with exercise across the HFpEF spectrum ( P < 0.05 vs. baseline), except when postcapillary pulmonary hypertension was present at rest ( P = 0.73 vs. baseline). A single sildenafil administration failed to increase circulating cGMP levels and did not improve RV performance. Conclusion: Exercise CMR identifies impaired RV‐arterial coupling at an early stage of HFpEF. Circulating cGMP levels phenocopy the haemodynamic spectrum in HFpEF but fail to increase after phosphodiesterase type 5 inhibition, endorsing the need for alternative interventions to increase cGMP signalling in HFpEF.